Human Rights Concept in Islamic Legal Thought - Dede Husni Mubarok; Alief Akbar Musaddad (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2020)
When the New Order regime fell, demands or aspirations for the formalization of Islamic law in Indonesia were intensively voiced by a group of Muslims, both through the political process and in interactions in the public sphere. However, other secular and Muslim groups are worried about the formalization of Islamic law because many provisions in sharia are considered inconsistent with the pillars of democracy and human rights, such as freedom, gender equality, equality of citizenship, and tolerance. The two seemingly contradictory poles are interesting to study through etymological and terminological approaches to the terms of the Shari’ah in the correlational interpretations of the Qur’an and Sunnah texts and the dynamics of their historical meanings so that it will give birth to the image of Islamic Shari’ah which is friendly, full of peace, and respect for human rights. Therefore, Islamic law, which is flexible, elastic, tolerant, and inclusive, can substantially be applied in the midst of multicultural, multi-religious, and multi-ethnic social realities in the context of upholding democracy and respecting human rights.